Pyrodinium bahamense var. compressum and other dinoflagellate cyst distribution in surface sediments of Cancabato Bay, Leyte, Philippines - Durante, Caryl Y. (2015)
This study provided an assessment of the abundance, distribution and density of dinoflagellate cysts present in the surface sediments of Cancabato Bay. Surface sediment samples were collected from 17 stations using a grab sampler and a gravity corer from November 2014 to March 2015. Sediments were collected for physicochemical characterization. Palynological technique was used for cyst processing. Cysts were viewed using light microscopy at 100x to 400x magnification. A total of 21 species of dinoflagellate cysts were identified and belonged to 5 groups: Gonyaulacoid, Protoperidinioid, Gymnodinioid, Calciodinellid and Diplopsalid. Cysts were detected in all stations, with cyst densities ranging from 1-80 cysts g raised to the power of -1 DW. Protoceratium reticulatum was the dominant species in 4 stations. Low levels of Prodinium bahamense var. compressum cysts were detected in 13 stations ranging from 0-16 cysts g raised to the power of -1 DW.